التخيل في شعر جميل بن معمر - موفق, سميرة (كلية الأدب العربي والفنون, 2024)
تنطلف هذه الرسالة من الشعر كأساس في تحديد طريقة تأثيره على المتلقي وحمله على التسليم والاذغان، وتتكل " على جميل بن معمر" كنمودج لشاعر مشهور في الغل العذري، فالتخييل لا يعرف الحجا بقدر ما يعرف الدّجى، لا يعرف العقل بقدر ما يعرف العاطفة والحب، فهو شعر يخاطب المشاعر والعاطف لما فيه من متعة تأثير وروعة وتصوير وجمال لفظ وحسن صياغة، هو الطاقات الايحادية، والمفجرات التصويرية، والانزياحات الشعرية والمحاكاة. تهدف هذه الدراسة إلى تسليط الضوء على الجانب التشكيلي الجمالي الذي طبع "شعر جميل بن معمر" في محاولة للشكف عن الصور المتصلة بهذا الجانب ومظاهرها وبنيتها، ومن ثمة تبيان التخييلية معايير القيم الجمالية وأسسها التشكيلية التي انبنى عليها الكون الشعر عنده"، وذلك من خلال دراسة تحليلية استقصائية تستند إلى قراءة الواعية الموضوعية. This message begins with poetry as a basis for determining the method of its influence on the recipient and making him submit to submission and adhan. It relies on “Jamil bin Muammar” as a model for a famous poet in virginal lust. Imagination does not know argument as much as it knows darkness. It does not know reason as much as it knows emotion and love. Poetry addresses feelings and emotions because of the pleasure, influence, splendor, imagery, beauty of pronunciation, and good wording. It is univocal energies, pictorial explosives, poetic shifts, and simulation. This study aims to shed light on the aesthetic plastic aspect that characterized “Jamil bin Muammar’s poetry” in an attempt to reveal the images related to this aspect and their appearances and structure, and from there to show the imaginary standards of aesthetic values ​​and their plastic foundations on which his poetry universe was built, through a study An investigative analysis based on objective, conscious reading.
Keywords: العقـــــــــــــــــــــل - الخيـــــــــــــــــــــــــــال - التخييـــــــــــــــــــــل -التصويـــــــــــــــــــر-المحاكـــــــــــــــــــــــــــاة; Mind -Imagination- Imagination-Photography -Simulation.